Studi Komparatif Implementasi Standar Prosedur Operasional Perawatan Pascaoperasi Di Dua Rumah Sakit Umum Daerah - Fatimah Naping; Bonar Adepapa Malamoy; Rifki Sakinah Nompo; Merlis Simon (Yayasan Healing and Healthcare Education, 2026)
A postoperative wound is an intentional tissue injury resulting from a surgical procedure. To mitigate subsequent surgical risks, nursing staff must stringently practice and comply with established Standard Operating Procedures (SOPs). This study employed a quantitative comparative design with a structured observational approach to evaluate adherence variations to these protocols. A total of 34 nurses were selected as respondents, divided equally between two distinct regional government healthcare institutions (17 respondents each). Data gathering was conducted via direct monitoring using an assessment checklist for surgical wound management. Due to the non-normal distribution of the numerical data, a non parametric Mann-Whitney test was performed. The statistical analysis demonstrated a highly significant variance in SOP compliance scores for wound care between the two health facilities (p = 0.005 < 0.05). Based on the mean rank evaluation, the first institution exhibited superior clinical performance and protocol comprehension compared to the second one. Conclusively, these findings indicate that differences in the effectiveness of clinical training programs, ongoing orientation, or internal supervisory methods at the first facility play a pivotal role in augmenting nursing competencies and discipline regarding postoperative wound management.